ETNOPEDAGOGI BADUY : PENDIDIKAN YANG MENUMBUHKAN KETANGGUHAN DAN KESEDERHANAAN - Novi Sopirah; Danik Mulya Sari; Ila Rosmilawati; Ujang Jamaludin (STKIP Subang, 2025)
This study examines the ethnopedagogical practices of the Baduy indigenous community as a model of traditional education that emphasizes the values of resilience and simplicity. Education in the Baduy community is not conducted through formal institutions, but through an intergenerational learning process rooted in customs, daily activities, and ancestral spirituality. Using a qualitative approach, data were collected through observation, in-depth interviews, and documentation involving community members and traditional leaders. The findings reveal that cultural values are transmitted through exemplary behavior, oral traditions, and direct involvement in communal life, which collectively shape character, self-discipline, environmental awareness, and social responsibility. The Baduy educational model prioritizes harmony with nature, adherence to customary law, and moral integrity over academic achievement. These ethnopedagogical practices demonstrate that local wisdom can function as an effective educational framework in forming resilient and value-oriented individuals. This study contributes to the discourse on alternative educational models by highlighting the relevance of indigenous knowledge systems as a foundation for character education and sustainable learning practices in the contemporary context.